2018
DOI: 10.1016/j.apm.2017.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Modeling congestion and service time in hub location problems

Abstract: In this paper, we present a modeling framework for hub location problems with a service time limit considering congestion at hubs. Service time is modeled taking the traveling time on the hub network as well as the handling time and the delay caused by congestion at hubs into account. We develop mixed-integer linear programming formulations for the single and multiple allocation versions of this problem. We further extend the multiple allocation model with a possibility of direct shipments. We test our models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 57 publications
0
42
0
Order By: Relevance
“…In the literature, one can find numerous extensions of the classical HLPs that arise from different practical situations. For example, a congestion has been addressed by adding a constraint to the queue length at hubs (Mohammadi et al 2011;Marianov and Serra 2003), imposing a service time limit at hubs (Alumur et al 2018), as well as by adding a nonlinear term in the objective. The HLPs with congestion have been solved either by using Lagrangian methods (Elhedhli and Wu 2010) or metaheuristics (Koksalan and Soylu 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, one can find numerous extensions of the classical HLPs that arise from different practical situations. For example, a congestion has been addressed by adding a constraint to the queue length at hubs (Mohammadi et al 2011;Marianov and Serra 2003), imposing a service time limit at hubs (Alumur et al 2018), as well as by adding a nonlinear term in the objective. The HLPs with congestion have been solved either by using Lagrangian methods (Elhedhli and Wu 2010) or metaheuristics (Koksalan and Soylu 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A further step forward for the research on the multi-capacity hub location problem is to discuss the relevance with the level of congestion. Reference [41] considers a CHLP with service time and congestion for both single allocation and multiple allocation cases. They assume that service time includes travelling time through the network and handling time at hubs.…”
Section: Hub Location With Multiple Capacitymentioning
confidence: 99%
“…Afterwards, the assumptions and the parameters are depicted in the remaining subsections, respectively. Our problem is inspired by the integrated research of hub location and revenue management developed by [19], the research on the hubs with multiple capacity levels based on [41], and the reseach on the disruptions considered by [7].…”
Section: Problem Statementmentioning
confidence: 99%
“…Research by Karimi and Setak (2018) showed in the problem of traffic scheduling and hub location routing, the hubs in the network are not completely interconnected, and the goal is to maximize the total traffic and minimize the total fixed cost and routing cost within the predetermined minimum arrival time. Research by Alumur, Nickel, Rohrbeck and Saldanha-da-Gama (2018)showed modeling framework for hub location issues considering hub crowded service time constraints. The service time model takes into account the running time, processing time and the delay caused by hub congestion.…”
Section: Hub-and-spoke Networkmentioning
confidence: 99%